2013
DOI: 10.22401/jnus.16.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Green Tea Extract on Histological Structure of Kidney, Pancreas and Adrenal Gland in Alloxan-Induced DiabeticMale Albino Rats

Abstract: Histological structure of kidney, pancreas and adrenal gland in alloxan-induced diabetic rats was investigatedafter daily oral administration of green tea water extract for 4 weeks. Forty adultmale albino rats Rattusnorvegicus, 12 weeks old, weighing 150-160 g were divided into 4 experimental groups: The first group was considered as negative control group. The second groups were affected by inducing experimental diabetes by intraperitonial injection of (150 mg/kg b.w) alloxan. The third group was considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Diabetes mellitus is a metabolic syndrome resulting from insulin deficiency, insulin resistance, or both [ 38 ]. According to the WHO, diabetes mellitus is a silent killer, affecting 1%–5% of the global population [ 39 ]. By 2025, the number of patients with diabetes is expected to exceed 325 million.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a metabolic syndrome resulting from insulin deficiency, insulin resistance, or both [ 38 ]. According to the WHO, diabetes mellitus is a silent killer, affecting 1%–5% of the global population [ 39 ]. By 2025, the number of patients with diabetes is expected to exceed 325 million.…”
Section: Discussionmentioning
confidence: 99%
“…World Health Organization (WHO) indicates that DM is one of the major killers of humans in our time and affect 1 –5% of the world population [ 3 4 ]. By the year 2025, the number of individuals with diabetes is predicted to be more than 325 million in spite of availability of new drugs, techniques and surgical intervention [ 5 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study using water extract of green tea as an antioxidant, the diabetic‐treated rats showed amelioration of the histopathological changes like fatty degeneration of renal tubule relative to diabetic rats. [ 63 ] The protective effect of BMFE may be due to its content of antioxidant components such as cyanidin 3‐glucoside [ 33,34,58 ] and cyanidin 3‐rutinoside [ 59‐61 ] that can reduce oxidative stress in the cells, resulting in normal structures and functions. [ 64 ]…”
Section: Discussionmentioning
confidence: 99%